Service design and knowledge management in the construction supply chain for an infrastructure programme - Duryan, Meri; Smyth, Hedley (Built environment project and asset management, 2019)
PurposeThe purpose of this paper is to determine the extent to which service design (SD) is addressed by the client and its supply chain at a program level into one functional capability, knowledge management (KM), to share knowledge across projects and organizational actors.Design/methodology/approachThe interpretative methodology employing two methods of engaged scholarship, namely, action research and engaged research, is applied. The data are analyzed using cognitive mapping to identify the extent of alignment of perceptions.FindingsThe findings show that the client and its supply chain are very transactional in their management minimizing investment in KM and program management. There is a lack of commitment and cultural leadership; hence, there is over-reliance on individuals to take responsibility for knowledge sharing and application. SD thinking can help develop a holistic approach to learning from projects.Research limitations/implicationsThe study underlines the links between the concepts of SD and KM. The findings emphasize the importance of developing a holistic approach to KM through the lenses of SD. The organizations must view KM as a process and build capabilities at a program level to make knowledge sharing an integral part of the work culture across projects.Originality/valueThe study contributes to the subject of KM in the construction industry by mobilizing the concept of SD to examine how KM systems and procedures are embedded in the client and across its supply chain.